Ponzi Scammer: Old Wine in New Bottles? - Taofik Hidajat; Thanh-Binh Phung (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
The purpose of this research is to learn how Ponzi scheme perpetrators recruit victims and to gain knowledge of the reasons why this fraud persists. This research used a qualitative methodology to collect data from Ponzi schemers. Most swindlers are the same people using various schemes, modes, and instruments. Public figures are used by scammers to build victims' trust, get access to various communities, and manipulate information. Public figures must be careful because scammers use them to attract victims. The novelty of this research is to fill the research gap on Ponzi schemes with a qualitative approach from the con artist's perspective.